Healing wonders of diet : effective guide to diet therapy - Varona, Blecenda Miranda; Tablante, Maria Elena; Varona, David Arsulo (Philippines : Philippine, Publishing House, 2003)
This book includes a list of common diseases as well as the health problems that may be managed at home during their onset and/or during recovery. A short description (What It) of the disease or health problem introduces you to its causes (Probable Causes), possible symptoms (Probable Symptoms), and finally to its dietary management (Helpful Dietary Management).
Includes index.
Keywords: Diet therapy; Cookbooks; dietary management; recipes